Metaphorical Thinking Profile of Middle School Students in Solving Mathematical Problems in terms of Students' Mathematical Ability - Makrufah, Siti; Fiangga , Shofan (Journal of Mathematical Pedagogy (JoMP), 2021)
Metaphorical thinking is a thinking process that can be used to get a more optimal understanding of a concept by involving some appropriate metaphors. This research is a descriptive study with a qualitative approach that aims to describe the thinking profile of junior high school students in solving mathematical problems. The subjects of this study were three students with high (ST), medium (SS), and low (SR) math abilities. Data was collected by presenting students' mathematical ability tests, problem-solving tasks, and semi-structured interviews. In general, the results in this study are the three subjects with high, medium, and low abilities in the stages of relating, exploring, analyzing, and transforming. but what makes the difference is that at the connected stage, high mathematics (ST) subjects have connected the two ideas they have, but moderate (SS) and low (SR) mathematics subjects have not been able to. And at the experience stage, ST and SS have made conclusions from the final results of the problems presented and can solve the problems faced by SR not yet able, junior high school students with high mathematical ability category have better metaphorical thinking processes than students with medium and low mathematics categories. Middle school students in the category of moderate mathematical ability have better metaphorical thinking processes than students with low ability categories.